If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -48 + -2x = 5x + 36 Reorder the terms: -48 + -2x = 36 + 5x Solving -48 + -2x = 36 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -48 + -2x + -5x = 36 + 5x + -5x Combine like terms: -2x + -5x = -7x -48 + -7x = 36 + 5x + -5x Combine like terms: 5x + -5x = 0 -48 + -7x = 36 + 0 -48 + -7x = 36 Add '48' to each side of the equation. -48 + 48 + -7x = 36 + 48 Combine like terms: -48 + 48 = 0 0 + -7x = 36 + 48 -7x = 36 + 48 Combine like terms: 36 + 48 = 84 -7x = 84 Divide each side by '-7'. x = -12 Simplifying x = -12
| h(-4)=-16(-4)2+88(-4)+2 | | -14k=-2k+2 | | x^2-100=10 | | 3.5=7.1-0.4x | | g+(-7)=21 | | 5y-4(x-y)= | | 1.005y=20.1 | | X^3+12x=12 | | 13x=17*-4 | | 2(x-5)+7(2x+5)=10x+11 | | 175+75=x | | .66x-2=20 | | 3(3n)+3(4)=54+6n | | 13x=17-4 | | 7w-3(4w-24)=11 | | -6+3x=19 | | 2(28)+3x-2=6x | | 7x-2.5+2.7x=12.8-1.6x | | 3x-2+8x-16=180 | | 8(x+7)+7(1+4x)=63 | | 6+4r=2r+3 | | X^2+x+1=-3x | | g(-2)=x^2-3x | | 2x+3(5x-7)=132 | | 8m+24=5m+27 | | 29-15x=-48 | | 9n+12=60n | | 10-.9(w-17)=.7(w-17) | | f(-3)=9(-3)-5 | | 3x-2+8x-16=10 | | 400=2X*20 | | 10+7v=3+8v |